(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
Data curation has emerged as a new area of responsibility for researchers, librarians, and information professionals in the digital library environment. This paper presents the preliminary findings of a large research project sponsored by the International Federation of Library Associations (IFLA), under the auspices of its Library Theory and Research (LTR) Section. The primary objective of the project is to identify the characteristic tasks and responsibilities of data curators in both international and interdisciplinary contexts. The ultimate objective, however, is to develop a “data curation ontology” that will better define the profession and support the development of educational curricula to train future data curators.